1995
DOI: 10.1111/j.1399-3011.1995.tb01056.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the in vitro and in vivo activity of the l‐, d,l‐ and d‐Cit6 forms of the LH‐RH antagonist Cetrorelix (SB‐75)

Abstract: The objective of this study was to examine the in vivo and in vitro gonadotropin‐inhibiting potencies, edematogenic activities and the receptor binding affinities of the d‐Cit6, d,l‐Cit6 and l‐Cit6 forms of the LH‐RH antagonist Cetrorelix (SB‐75) [AC‐d‐Nal(2)1,d‐Phe(4Cl)2,d‐Pal(3)3,d‐Cit6,d‐Ala10]LH‐RH. In order to demonstrate the suppressive effects of two different diastereomers of SB‐75 and their racemic mixture on LH and FSH release, [d‐Cit6] SB‐75 was injected subcutaneously in doses of 2.5 and 10 μg/rat,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…GnRH III has been shown that it has lower endocrine effect in mammals than the human GnRH (GnRH-I, also called LH–RH), it binds to the GnRH receptors on cancer cells and exhibits anti-proliferative effect on many types of GnRH receptor-positive tumors. lGnRH-III contains only L-amino acids, which are presumable to avoid undesirable edematogenic activity [23]. These data indicate that the therapeutic use of lGnRH-III has lower risk of complications than the application of GnRH analogs.…”
Section: Discussionmentioning
confidence: 99%
“…GnRH III has been shown that it has lower endocrine effect in mammals than the human GnRH (GnRH-I, also called LH–RH), it binds to the GnRH receptors on cancer cells and exhibits anti-proliferative effect on many types of GnRH receptor-positive tumors. lGnRH-III contains only L-amino acids, which are presumable to avoid undesirable edematogenic activity [23]. These data indicate that the therapeutic use of lGnRH-III has lower risk of complications than the application of GnRH analogs.…”
Section: Discussionmentioning
confidence: 99%